Polychlorinated dibenzodioxins, dibenzofurans, and biphenyls in fresh water fish from Campania Region, southern Italy - Pacini, N.; Abate, V.; Brambilla, G.; De Felip, E.; De Filippis, S.P.; De Luca, S.; di Domenico, A.; D’Orsi, A.; Forte, T.; Fulgenzi, A.R.; Iacovella, N.; Luiselli, L.; et al. (Chemosphere (Oxford), 2013)
► Freshwater fish from Campania Region were analyzed as bioindicators of dioxins/PCBs. ► Results of benthic and pelagic species were subject to hybrid cluster analysis. ► Both benthic and pelagic fish may be good indicators of environmental contamination. ► Two exposure macro-areas were identified north and south of Naples. ► Samples were compliant with food regulation despite a history of local contamination. Twenty-eight fish muscle specimens from the main water bodies of the Campania Region were analyzed in our laboratory. On average, results showed a low contamination by PCDDs+PCDFs and a relatively more important presence of DL-PCBs. All specimens were compliant with EU regulatory maximum levels. Cumulative PCDD+PCDF+DL-PCB concentrations (TEQTOT) were comprised in the range 0.223–11.4 pgWHO97–TEQg−1 fresh weight (fw). DL-PCB contribution to TEQTOT was on average greater than 86% (range, 50.2–97.1%). The cumulative concentrations of 30 non-dioxin-like PCB congeners (Σ30(NDL-PCBs)) and of the six indicators (Σ6(NDL-PCBs)) were respectively in the ranges 3.30–515 and 1.30–195ngg−1fw. The hybrid clustering approach adopted to analyze the sample-specific congener profiles indentified the main analytical patterns present in the database and, in particular, two main diverse exposure macro-areas that seem to exist north and south of the city of Naples. The distribution of PCDD and PCDF congeners among different species showed significant variations from chub (Leuciscus cephalus), characterized by a higher proportion of low-chlorinated congeners (e.g. 2,3,7,8-T4CDD), to eel (Anguilla anguilla), whose contamination consisted mainly of highly chlorinated congeners (e.g. O8CDD). To have a more complete perspective in relation to the contaminants present in the environment, the study suggestion is to use benthic as well as pelagic species to obtain an integrated characterization of fish tissue contamination.